Proceedings of the Eleventh European Conference on Computer Systems 2016
DOI: 10.1145/2901318.2901322
|View full text |Cite
|
Sign up to set email alerts
|

On the capacity of thermal covert channels in multicores

Abstract: Modern multicore processors feature easily accessible temperature sensors that provide useful information for dynamic thermal management. These sensors were recently shown to be a potential security threat, since otherwise isolated applications can exploit them to establish a thermal covert channel and leak restricted information. Previous research showed experiments that document the feasibility of (lowrate) communication over this channel, but did not further analyze its fundamental characteristics. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 33 publications
0
61
0
Order By: Relevance
“…Our experiments show that compared similar cover channels, like the thermal covert channel [2], the power covert channel channel allows a higher throughput but is less robust to disturbances by other applications on the platform.…”
Section: Robustnessmentioning
confidence: 93%
See 2 more Smart Citations
“…Our experiments show that compared similar cover channels, like the thermal covert channel [2], the power covert channel channel allows a higher throughput but is less robust to disturbances by other applications on the platform.…”
Section: Robustnessmentioning
confidence: 93%
“…In a similar work, Masti et al [10] showed the possibility of such a temperature based covert channel within a processor, to establish a data transmission between different application which are run sequentially on the same core or between two different cores in a multicore system. Bartolini et al [2] later analysed these covert channels between multiple cores in a processor in detail. The authors derived capacity bounds for the different inter-core channels in the order of 300 bits per second (bps) and presented an improved implementation of the covert channel that achieved a throughput of up to 50 bps with less than 1% error probability.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has examined how to share information over covert channels, such as across virtualized environments on cloud systems [59], using L1 and L2 cache to share information [44], measuring temperature to create a thermal covert channel [35], [5], and taking advantage of processor architecture to leak information [57]. This includes using the branch predictor itself as a covert channel [15], [13], which ExSpectre similarly uses.…”
Section: B Covert Channelsmentioning
confidence: 99%
“…Hasan et al [26] conducted a heat based attack on Simultaneous Multithreading (SMT) by repeatedly accessing a shared source to create a hotspot in one malicious thread. Thermal covert channel attacks based on CPU cores' temperature variations have been presented in [39], [16]. While these works provide a guidance on thermal attacks on individual components, they do not study the impacts of thermal attacks on servers and data centers.…”
Section: Related Workmentioning
confidence: 99%